2023
DOI: 10.3389/fpubh.2023.1242314
|View full text |Cite
|
Sign up to set email alerts
|

Costs and resource needs for primary health care in Ethiopia: evidence to inform planning and budgeting for universal health coverage

Abebe Alebachew,
Engida Abdella,
Samuel Abera
et al.

Abstract: IntroductionThe Government of Ethiopia (GoE) has made significant progress in expanding access to primary health care (PHC) over the past 15 years. However, achieving national PHC targets for universal health coverage will require a significant increase in PHC financing. The purpose of this study was to generate cost evidence and provide recommendations to improve PHC efficiency.MethodsWe used the open access Primary Health Care Costing, Analysis, and Planning (PHC-CAP) Tool to estimate actual and normative re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Recent studies conducted in Afghanistan ( 38 ), Ethiopia ( 31 ), and Kenya ( 32 ) have similarly examined the actual and normative costs of PHC service packages. Consistent with our research, they revealed substantial resource gaps between existing PHC resources and the financial requirements to provide quality PHC services to all those who need them.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies conducted in Afghanistan ( 38 ), Ethiopia ( 31 ), and Kenya ( 32 ) have similarly examined the actual and normative costs of PHC service packages. Consistent with our research, they revealed substantial resource gaps between existing PHC resources and the financial requirements to provide quality PHC services to all those who need them.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the World Health Organization’s PHC Measurement Framework and Indicators ( 30 ), key metrics that can be analyzed in the PHC-CAP Tool include inpatient and outpatient services per clinical staff, daily service output per clinical staff, cost per input, cost per service, total cost, and cost per capita—contingent on data availability. Aside from Nigeria, the PHC-CAP Tool has also been used in five additional countries, including Ethiopia ( 31 ) and Kenya ( 32 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations